ESTABLISHMENT OF MULTIPLEX PCR ASSAY FOR SIMULTANEOUS DETECTION OF SALMONELLA SPP., SHIGELLA SPP. AND ENTAMOEBA HISTOLYTICA (Vietnam Journal of Community Medicine, 2022)
Objective: To establish a novel multiplex PCR assay for simultaneous detectionof foodborne pathogens, including Salmonella spp., Shigella spp., and Entamoebahistolytica, with high sensitivity, specificity, cost-effectiveness and time-saving.Method: Multiplex PCR, Semi-Nested PCR and melting analysis for specificallyamplifying and distinguishing three highly conserved target gene regions (invA,ipaH, 18S rRNA), in order to simultaneously detect Salmonella spp., Shigella spp.,Entamoeba histolytica in a single reaction tube. Specific pathogens are characterizedbased on the melting profiles of the PCR products collected on a realtime PCRinstrument following the second round of amplification.Results: The established multiplex PCR assay is capable of simultaneously detectingSalmonella spp., Shigella spp., and Entamoeba histolytica at a limit of detection of5.86 copies/µl, 24.4 copies/µl và 53.6 copies/µl, respectively (confidence interval of95%), the specificity reached 100% when evaluated with multiple microbial speciesprovided by the Department of Microbiology, 103 Military Hospital.Conclusion: The novel multiplex PCR assay for simultaneous detection of Salmonellaspp., Shigella spp., Entamoeba histolytica has been successfully established.
Keywords: Multiplex PCR, Semi-Nested PCR, Salmonella spp., Shigella spp., Entamoeba histolytica.